Knowledge and Practices Relating to Acute Pesticide Poisoning Among Health Care Providers in Selected Regions of Tanzania - Elikana Lekei; Aiwerasia V Ngowi; Habib Mkalanga; Leslie London (SAGE Publishing, 2017)
Background: Acute pesticide poisoning (APP) is commonly underdiagnosed in Tanzania. Studies in developing countries suggest that a lack of diagnostic skills among health care providers (HCPs) undermines surveillance for APP. This study aimed at characterizing experience and skills of Tanzanian HCPs regarding APP diagnosis and management. Methodology: The population included HCPs responsible for managing APP in Kilimanjaro and Arusha regions (n = 91). The resulting sample included 66 respondents (response rate: 73%). The data were collected in 2005 using a standardized questionnaire. Results: Half of all respondents (50%) reported handling at least 1 APP case with 15% reporting handling more than 5 cases in the past. Reported experience of handling an APP case was marginally higher in respondents who reported ⩾4 years of work experience in the health sector compared with those with <4 years of work experience (odds ratio = 1.32; 95% confidence interval = 0.9-1.5). Most of the respondents had high knowledge of exposure routes, reporting awareness of oral (98.5%), inhalational (93.9%), and dermal (77%) routes. The study revealed low awareness of pesticide classification by chemical groups (29%) or World Health Organization hazard (0%) and weak knowledge on pesticide label instructions (55%). Organophosphates accounted for 35% of the pesticide products reported by respondents as being responsible for poisoning. Some treatment options were incorrectly reported as first aid options, and some reported first aid options were wrong or inappropriate. Conclusions: The study revealed that HCPs in northern Tanzania lack adequate skills to diagnose and manage APP. For effective surveillance of APP, there is a need to include training on hazards, classification, diagnosis, and health effects in the training programmes for all HCPs in Tanzania.